A systematic review of qualitative studies capturing the subjective experiences of Gay and Lesbian individuals’ of faith or religious affiliation - Wilkinson, Dean J. (Mental health, religion & culture, 2020)
Individuals identifying as religious tend to report better health and happiness regardless of affiliation, work and family social support or financial status. Evidence suggests that cultural factors are intertwined with these concepts. Exploration of sexual minorities' experiences has been neglected. Recently, a body of evidence is developing concerning this population, with theoretical speculation for changes of "stressors" for future generations and implications, particularly, on mental health. Lesbian and Gay (LG) individuals of faith (or spirituality) are susceptible to unique "stressors"; however, religion can provide a support network providing protective health benefits. This review systematically explores the existing evidence for the subjective experiences and accounts of LG people of faith. Sexual minority individuals who follow a religion or faith can experience good social support, reducing the risk of negative health outcomes, while for others, potentially serious, negative mental and physical health consequences are experienced (e.g., internalised homophobia, anxiety, rejection and suicidal ideation).